NOTE ON THE WIDESPREAD BLEACHING OBSERVED AT THE MANUEL LUIZ MARINE STATE PARK, MARANHÃO, BRAZIL - Amaral, Fernanda D.; Hudson, Marco; Steiner, Andrea (Arquivos de Ciências do Mar, 2017)
Here we present a first record of widespread coral bleaching off the northern coast of Brazil, in the Manuel Luiz Marine State Park. During an expedition to find cnidarians in June 1998 high scleractinian and calcified hydroid diversity was encountered, a richness that in Brazil can only be compared to the Abrolhos, Bahia State): four species of calcified hydroids, twelve species of scleractinian corals, two species of sea-anemones, one species of zoanthid, and one species of octocoral. However, three of the four species of calcified hydroids observed (Millepora alcicornis, M. braziliensis, and Millepora sp.) were bleached or dead and covered by algae and/or invertebrates. Similarly, among the scleractinian corals, bleaching was observed in specimens of eleven of the twelve species recorded (Madracis decactis, Agaricia agaricites, A. fragilis, Siderastrea stellata, Porites astreoides, P. branneri, Favia gravida, F. leptophylla, Montastrea cavernosa, Meandrina braziliensis, Mussismilia hispida, and Scolymia wellsi). Bleaching was associated with elevated average monthly sea surface temperatures, which was at least 1ºC higher than the previous year, and at least 1ºC above the expected maximum monthly mean, according to remotely sensed data available online from NOAA (National Oceanic and Atmospheric Administration)